HISTOPATHOLOGICAL ASPECTS OF UNDER-DENTURE ORAL MUCOSA AREA IN ACRYLIC REMOVABLE DENTURES WEARERS - Răzvan Eugen Ghiță; Veronica Mercuț; Sanda Mihaela Popescu; Oana Cella Andrei; Andreea Stănuși; Ileana Cristiana Petcu; Iulia Roxana Marinescu; Roxana Maria Pascu; Mihaela Niculescu; Monica Scrieciu (Romanian Society of Oral Rehabilitation, 2022)
Aim of the study:The aim of this study was to highlight the histopathological lesions of the oral mucosa adjacent to acrylic removable denture. Material and methods: The histopathological study was performed on 21 fragments of human oral mucosa, collected from subjects wearing removable acrylic dentures, who presented at the Clinic of Dental Prosthetics and Oral Rehabilitation of the Faculty of Dentistry in Craiova, between January 2018 and May 2020. Results: The most common lesions in the epithelium were acanthosis, parakeratosis, associated with the presence of papillomatosis and hypertrophy of connective papillae. The lesions of the lamina propria were mostly of the chronic granulomatous inflammatory type or of the lymphoplasmocytic type, with macrophages in some places. Conclusions: The possibilities of the oral mucosa to react in the contact area with a removable partial acrylic denture are multiple, ranging from simple adaptive histopathological changes to the appearance of acute or chronic histopathological lesions.